Faktor-Faktor Yang Mempengaruhi Pengungkapan Tanggung Jawab Sosial (CSR) Dalam Laporan Tahunan Perusahaan (Studi Kasus Perusahaan Indeks LQ 45) - admin, YAHYUMI B11111020 (Jurnal Manajemen Update, 2016)
This study was aimed at finding out the effect ofÂ  institutional ownership, debt to equity ratio, and board size on corporate social responsibility disclosure in annual reports of indeks LQ 45 corporations in the 2010-2013 period. The sampling technique used was purposive sampling by selecting sample that has been predetermined based on the intention and purpose of the study during the study period. The data analysis technique used was Multiple Linear Regression Analysis; the data analysis was aided by SPSS 16 program. The results showed that (1) there is a significant and positive (+) effect of institutional ownership on social responsibility disclosure, (2) there is a not significant and negative (-) effect of debt to equity ratio on social responsibility disclosure, (3) there is a significant and negative (-) effect of board size on social responsibility disclosure and (4) there is a significant effect of corporation institutional ownership, debt to equity ratio and board size on corporate social responsibility disclosure. Â  Keywords: Institutional Ownership, Debt to Equity Ratio, Board Size, corporate social responsibility disclosure. Â